Modelado de red hidrosanitaria de aprovechamiento de aguas lluvias y agua grises para la ciudad de Bogotá en edificios multifamiliares tipo VIS (2022)
A system for the use of rainwater and gray water is modeled in order to generate a decrease in the exploitation of drinking water in the city of Bogotá de Colombia for a 7-story VIS type multifamily building with 4 apartments per floor; This model comprises independent stormwater supply networks and drinking water, hydropneumatic pumping system for these networks, pretreatment of Grease trap for rainwater before supplying the network and appliance use of gray water.